2006
DOI: 10.2134/agronj2006.0085
|View full text |Cite
|
Sign up to set email alerts
|

Winter Pea and Lentil Response to Seeding Date and Micro‐ and Macro‐Environments

Abstract: Winter pea (Pisum sativum L.) and lentil (Lens culinaris Medik.) have potential agronomic advantages over spring types in the Pacific Northwest (PNW) and northern Great Plains (NGP). The objectives of this study were to: (i) determine suitable seeding date and cereal stubble height in no‐till systems for winter pea and lentil; (ii) quantify and compare biomass and seed yield of winter pea and lentil with spring types; and (iii) compare adaptation of winter pea and lentil between the PNW and the NGP. Two breedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 24 publications
3
47
0
1
Order By: Relevance
“…Such observations of higher yield potential with WP compared to spring pea are not in general agreement with the much more comprehensive data sets from the Canadian and US northern Great Plains where winter temperatures are considerably colder than in the PNW. Chen et al (2006) found that WP cultivars did not have a yield advantage over spring pea in central and south-central Montana. Similarly Strydhorst et al (2015) recommended that farmers consider WP over spring pea only in the southernmost locations in Alberta.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Such observations of higher yield potential with WP compared to spring pea are not in general agreement with the much more comprehensive data sets from the Canadian and US northern Great Plains where winter temperatures are considerably colder than in the PNW. Chen et al (2006) found that WP cultivars did not have a yield advantage over spring pea in central and south-central Montana. Similarly Strydhorst et al (2015) recommended that farmers consider WP over spring pea only in the southernmost locations in Alberta.…”
Section: Introductionmentioning
confidence: 87%
“…Pulse crops are cool-season annual grain legumes mostly grown in the northern tier states of North Dakota and Montana, the high-precipitation (>450 mm average annual) Palouse region of Washington and Idaho (NASS, 2017), and the Canadian provinces of Alberta, Saskatchewan, and Manitoba (Statistics Canada, 2017). During the past 20 years, pulse crops have become an integral component of diversified and profitable dryland cropping systems in the Canadian and US northern Great Plains (Miller et al, 2003(Miller et al, , 2015Chen et al, 2006;Long et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomass production is critical for maintaining seed-zone soil moisture in notill fallow. Chen et al (2006) demonstrated that tall stubble improved yields of winter lentil (Lens culinaris). Producers normally grow short, semi-dwarf varieties of winter wheat in this area, however, some farmers are starting to grow tricale (×Triticale Wittmack) which produces 50% more crop residue than semi-dwarf wheat in high residue farming systems (Port, 2016).…”
Section: Reduced Tillage and Crop Residue Managementmentioning
confidence: 99%